Politik Islam di Afghanistan: Studi terhadap Kekuasaan Kelompok Taliban - Septian Fatianda (Local History & Heritage, 2023)
Afghanistan is a Muslim country with a long history of conflict. Politics in Afghanistan has always been characterized by repeated coups against the ruling leaders. Since 1994, a group of Afghan religious students formed an extremist group called the Taliban. This group even became the sole ruler of the country after the coup against Ashraf Gani in 2021. This paper aims to examine the embryo of the conflict that led to the emergence of the strong Taliban group in Afghanistan. The research method used in this study is a historical method with four steps: heuristics, source criticism, interpretation, and historiography. The results show that Afghanistan has never stopped fighting. In the current context, the Taliban has become an authoritarian ruler, and political and security conditions in Afghanistan are far from conducive. Women have been the group most affected by policies that restrict their rights.